Spectral and Waveform Cross-Correlation Analysis of Volcanic Tremor from The 2016 Eruption at Bromo Volcano, East Java - Meidi Arisalwadi; Sukir Maryanto; Hetty Triastuty (Natural B, Journal of Health and Environmental Sciences, 2017)
Bromo volcano is one of a series of active volcanoes in Indonesia, located on the Tengger caldera, Probolinggo, East Java. Bromo volcano has increased volcanic activity in the end 2015 until early 2016. The research was conducted to determine the characteristics of volcanic tremors. The methods used to determine the characteristics of volcanic tremors are spectral analysis and cross-correlation waveform analysis. Spectrogram analysis obtained frequency value 1-8 Hz for volcanic tremor of Bromo Volcano. From the results of spectral analysis volcanic tremor, it’s can be seen the value of the frequency peaks irregular means the type of spasmodic tremor. Based on the pattern of the peaks of the tremor spectral analysis using 3 stations having the same pattern and the analysis of cross-correlation waveform volcanic tremor of Bromo volcano was indicated from the same source mechanism because the correlation coefficient value is good that ranged about 0.6 – 0.8.